2013
DOI: 10.1111/1467-9248.12090
|View full text |Cite
|
Sign up to set email alerts
|

The Politicization of European Integration: More than an Elite Affair?

Abstract: A growing literature in research on the European Union (EU) claims that European integration has become comprehensively politicized in the EU's population. The most convincing evidence for this assertion stems from research on political and societal elites – studies of party manifestos, interest groups' activities, news media reporting and the like. By contrast, evidence on politicization trends in the broader citizenry is much more ambiguous. This article raises the question of whether politicization is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 47 publications
2
73
0
Order By: Relevance
“…These manifestations of actor engagement are time and place specific. They result in different patterns of politicisation with respect to the relative strength of salience and polarisation in various settings, the specific constellation of actors and audiences, the behavioural manifestations of politicisation and its substantive content (see also De Wilde and Zürn 2012;Hurrelmann et al 2013). …”
Section: Dimensions Of Variation In Politicisationmentioning
confidence: 99%
“…These manifestations of actor engagement are time and place specific. They result in different patterns of politicisation with respect to the relative strength of salience and polarisation in various settings, the specific constellation of actors and audiences, the behavioural manifestations of politicisation and its substantive content (see also De Wilde and Zürn 2012;Hurrelmann et al 2013). …”
Section: Dimensions Of Variation In Politicisationmentioning
confidence: 99%
“…In this arena, where political parties compete for votes, expansion of the scope of actors means that not only party‐affiliated actors in government address European integration, but also party actors that are not represented in government (for example, actors from opposition parties). However, we should keep in mind that political controversy in the electoral arena necessarily has an elitist bias and may not represent the full scope of political conflict on an issue which may include the activities of interest groups, social movement organizations and the wider citizenry (see, for instance, Hurrelmann et al ., forthcoming).…”
Section: Conceptualizing Politicization In the European Contextmentioning
confidence: 99%
“…More recently, scholars have started to focus on the communicative role of national parliaments in the EU, stressing their potential to make EU political decisions and processes more accessible for their citizens (see, for example, the Special Issue edited by Auel and Raunio, 2014). As Hurrelmann et al (2015) have found, increased salience of EU issues coupled with limited knowledge about the EU can lead to citizens experiencing a diffuse but deep feeling of disenfranchisement. Here, national parliaments have the ability to make EU politics more visible by functioning as a public 'Congress of Opinions' (Mill, 1865) on EU politics, and thus act as a remedy for such feelings of disenfranchisement: by controlling their executives and holding them publicly to account for their decisions at the EU level, they may help to attribute responsibilities in a multilevel polity that is perceived as complex, remote and opaque.…”
Section: National Parliaments Communication and The Media In Eu Affairsmentioning
confidence: 99%